LIPRIMAR®. FIFTEEN YEARS OF EVIDENCE - A. V. Susekov; N. V. Khokhlova (Рациональная фармакотерапия в кардиологии, 2016)
The evidences for statin use in cardiology are presented. Especially hypolipidemic efficacy of atorvastatin is demonstrated in according to comparative studies. Results of clinical studies on atorvastatin efficacy and safety in different groups of patients are also presented.